Changes in muscle recruitment, functional strength and ratings of perceived effort during an 8-over bowling spell: impact on performance - Barford, Gareth Charles (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Background: The musculoskeletal demands placed on the lower limb musculature of fast bowlers over time have not received much attention. In particular, measures of muscle recruitment changes have, to the author's knowledge, not been considered. Objective: The present study, therefore sought to establish any associations between an eight over, simulated fast bowling spell, and muscle activation patterns, power output, perceptual demands, and changes in performance. This will enable improvements in the development of training programmes. Methods: Players' were required to attend two sessions in total. The purpose of the initial session was to collect specific demographic, anthropometric and physiological data and injury history information from each player. In addition, this first session allowed for habituation with the treadmill, the jump meter and all other equipment involved in experimentation. The second testing session involved electrode attachment sites being identified on player's dominant leg. The areas were then shaved, wiped with an alcohol swab and left to dry, to ensure good connectivity. Pre- and post- measures of muscle activity and functional strength of the lower limbs were recorded in the Department of Human Kinetics and Ergonomics. The protocol took place at the Kingswood High Performance Centre, which is in close proximity to the initial testing site. The protocol involved players bowling eight overs (48 balls). During the protocol, accuracy, ball release speed and perceptual measures were recorded at the end of each over. After the protocol, players were driven back to the Human Kinetics and Ergonomics Department where post-testing measures were completed. The dependable variables of interest were muscle activation, functional strength of the lower limbs, 'local' ratings of perceived exertion (RPE), body discomfort, accuracy, and ball release speed. Results: For all muscles it was shown that, as the speed increased so did the muscle activity in players' lower limbs. There were no significant changes in muscle activity preversus post-protocol. There was however, a general trend of decreasing muscle activity post protocol at higher testing speeds. There were significant (p<0.05) decreases in peak power following the simulated eight over bowling spell. 'Local' RPE displayed a significant (P<0.05) increase with each additional over and were observed to reach the 'heavy' category. The players' highest discomfort area was in the lower back, with 13 players perceiving discomfort in this region following the eight over spell. The shoulder and chest were another two areas player's indicated discomfort with eight players selecting the dominant shoulder. Seven players complained of the dominant side pectoral muscle, leading foot and dominant latissimus dorsi muscle being uncomfortable. Interestingly, the dominant pectoral showed the highest body discomfort ratings amongst players. There were no significant changes in accuracy between overs although there were large interindividual differences in accuracy points between players. The decrease in ball release speed observed during over seven was shown to be significantly (p<0.05) lower than overs one to four. Conclusion: The power output and perceived strain results of the players, appears to indicate the presence of fatigue in players. However, the results are not conclusive, as the fatigue was not shown in muscle recruitment patterns, as well as the body discomfort ratings. There was a non-significant trend observed in the lower limb muscle activation decreasing at higher speeds. Players were able to maintain accuracy. However, the significantly lower ball release speed observed during over seven showed players performance decreasing.
Keywords: Cricket -- Bowling; Sports -- Physiological aspects; Muscles -- Wounds and injuries; Fatigue; Physical fitness; Cricket injuries